KAJIAN YURIDIS UNDANG-UNDANG NOMOR 18 TAHUN 2017 TENTANG PELINDUNGAN PEKERJA MIGRAN INDONESIA - LELISARI, LELISARI; IMAWANTO, IMAWANTO; FAHRURROZI, FAHRURROZI (Universitas Mahasaraswati Mataram, 2019)
Since the enactment of Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers (PPMI Law), there is a new term as a substitute for Indonesian Labor (for the next term TKI) to become Indonesian Migrant Workers (hereinafter referred to as PMI). By carefully reading the law governing TKI or PMI, namely Law Number 18 of 2017 concerning PPMI, it is made to correct various weaknesses in Law No. 39 of 2004, in which the main objective is to improve the law. thus TKI or PMI are increasingly protected. In fact, this law also still has some weaknesses. The research objective is to analyze weaknesses in Law No. 18 of 2017 concerning PPMI. The method used is a normative juridical research method with a statute approach and a conceptual approach. From the results of the study, there are five weaknesses in the PPMI Law, namely: There is inconsistency in implementing the rules, the PPMI Law still holds potential institutional conflicts regarding the authority of Ministries and Institutions / Non-Ministerial Bodies in the management of migrant workers protection, Articles in the PPMI Law concerning coaching and supervision also has the potential to be a rubber article because it does not elaborate on what forms of supervision and supervision should be carried out. There is no specific article that affirms the specific needs of PMI protection (especially women) who work in the domestic sector. Regulations regarding legal assistance for PMI are not regulated in detail. As a suggestion to immediately revise the PPMI Law, then it must be guarded and completed 27 regulations derived from the mandate of the PPMI Law consisting of 12 Government Regulations, 11 Ministerial Regulations, 3 Agency Regulations and 1 Presidential Regulation